PERBEDAAN PERILAKU IBU DALAM MELAKUKAN KUNJUNGAN IMUNISASI LANJUTAN ANAK BALITA SEBELUM DAN SESUDAH PENYULUHAN KESEHATAN DI WILAYAH KELURAHAN PASAR BARU KOTA TANGERANG TAHUN 2018 - Silfia Nuzulus Saidah; Endang Sri Wahyuni (Universitas Yatsi Madani, 2018)
Background: Based on the resul t of continued immunization coverage of DPT HB Hib in Pasar Baru urban village in 2017 as much as 31,7% with government target as much as 80%. From the data it can be seen that there is a gap between the total number of infants to the number of under - five children immunized by percentage. Objective: The purpose of this research is to know the difference of mother's behavior in conducting follow - up immunization visit of children under five before and after health counseling in Pasar Baru Urban Area Tangerang City Year 2018. Research Methods: The type of research used is Quasi Experimental research, with the design of One Group Pretes - Postest design. The population in this study were all mothers who had infants aged 18 months to 2 years who had not received DPT - HB - Hib booster immunization in the Pasar Baru Public Health Institution of Tangerang during January - February 2018 ie 20 infants who were overall used as research samples (total sampling). The analytical technique used is univariate to obtain the character istics of each demographic and bivariate variables used to determine the relationship between research variables. Result: Based on the analysis result, it is known 1) Majority of mother's behavior in conducting follow - up immunization visit before giving he alth education is negative (less good) as many as 12 people (60%). 2) Majority of mother's behavior in conducting follow - up immunization visit for under - five children after health education is positive (good) as many as 17 people (85%). 3) There is a signi ficant difference between mother's behavior in conducting follow - up immunization visit of children under five before and after health counseling, with value (p - value) 0,002. Suggestion: For mothers to be expected to be more active in finding information abo ut immunization and schedule of immunization for children so that there are no children whose immunization is incomplete through books, health workers or from other people's experiences for more attitude towards immunization